Biomarkers Correlate With Body Composition and Performance Changes Throughout the Season in Women's Division I Collegiate Soccer Players - McFadden, Bridget A.; Walker, Alan J.; Arent, Michelle A.; Bozzini, Brittany N.; Sanders, David J.; Cintineo, Harry P.; Bello, Marissa L.; Arent, Shawn M. (Frontiers in Sports and Active Living, 2020)
The purpose of this study was to evaluate the effects of a competitive soccer season on biomarkers and performance metrics in order to determine the correlation between changes in biomarkers, body composition, and performance outcomes. Twenty-one Division 1 female collegiate soccer players were monitored throughout the 16-week season. Player workload was measured using heart rate and Global Position Satellite systems at all practices and games. Performance testing, including vertical jump, VO2max, and 3-repetition maximum testing for bench press, squat and deadlift, occurred prior to pre-season and immediately post-season. Blood draws occurred prior to preseason and every 4-weeks thereafter, following a game. Body composition was assessed prior to the start of season (week 0) and weeks 6, 10, 14, and 17 (post-season). Delta area under the curve was calculated for biomarkers and body composition variables to account for seasonal changes adjusted for baseline. Pearson-product moment correlations were used to assess relationships with significance set at p < 0.05. Trends were considered p ≤ 0.10. No significant time main effects were seen for anabolic biomarkers (p > 0.05). Significant time effects were seen for catabolic biomarkers throughout the season (p = 0.001). No changes in body weight, VO2max, vertical jump, and deadlift occurred. Squat and bench press improved (p = 0.01 and p = 0.02, respectively) with a decline in percent body fat (p = 0.03) and a trend for increased fat free mass (p = 0.09). Additionally, total cortisol (TCORT) negatively correlated with fat free mass (r = −0.48; p = 0.03) and positively correlated with VO2max (r = 0.47; p = 0.04). A trend was shown for a positive correlation between both TCORT and free cortisol (FCORT) and percent body fat (r = 0.39; r = 0.40; p = 0.08, respectively). IGF-1 and growth hormone positively correlated to deadlift (r = 0.57; P = 0.02 and r = 0.59; p = 0.03), whereas creatine kinase showed a trend for a positive correlation with deadlift (r = 0.49; p = 0.06). IL-6 negatively correlated with bench press (r = −0.53; p = 0.03). These findings support a relationship between biomarkers, performance outcomes, and body composition. Biomarker monitoring may be useful to detect individual player's physiological response to an athletic season and may help provide insights in efforts to optimize performance outcomes.